Pengaruh Model Pembelajaran Kelompok Dan Individu Terhadap Gerak Dasar Menggiring Bola - Robert Romulus Silaban; Akor Sitepu; Ade Jubaedi (JUPE (Jurnal Penjaskesrek), 2018)
This study aims to determine the effect of group and individual learning models on basic motion of dribbling ball in male students of class VII of SMP 12 Bandar Lampung. This research is Population Research. Data collection techniques use tests and measurements. Research Population Is Male Students of Class VII of SMPN 12 Bandar Lampung totaling 30 Students. Instrument used by soccer dribble test. Data Analysis Using Test T. Research Results show that; (1) There is an Influence Between Group Learning Models Against the Basic Motion of Bringing the Ball in Male Students of Class VII of SMPN 12 Bandar Lampung. (2) There is an Influence Between Individual Learning Models on the Basic Motion of Bringing the Ball in Male Students of Class VII of SMPN 12 Bandar Lampung. (3) The Group Learning Model Is More Influential on the Basic Motion of Bringing the Ball to Male Students of Class VII of SMPN 12 Bandar Lampung.Penelitian ini bertujuan untuk mengetahui Pengaruh Model Pembelajaran Kelompok Dan Individu Terhadap Gerak Dasar Menggiring Bola Pada Siswa Putra Kelas VII SMPN 12 Bandar Lampung. Penelitian ini adaalah Penelitian Populasi. Teknik Pengumpulan Data menggunakan tes dan pengukuran. Populasi Penelitian Adalah Siswa Putra Kelas VII SMPN 12 Bandar Lampung yang berjumlah 30 Siswa. Instrumen yang digunakan soccer dribble test. Analisis data Menggunakan Uji T. Hasil Penelitian menunjukkan bahwa; (1) Ada Pengaruh Antara Model Pembelajaran Kelompok Terhadap Gerak Dasar Menggiring Bola Pada Siswa Putra Kelas VII SMPN 12 Bandar Lampung. (2) Ada Pengaruh Antara Model Pembelajaran Individu Terhadap Gerak Dasar Menggiring Bola Pada Siswa Putra Kelas VII SMPN 12 Bandar Lampung. (3) Model Pembelajaran Kelompok Lebih Berpengaruh Terhadap Gerak Dasar Menggiring Bola Pada Siswa Putra Kelas VII SMPN 12 Bandar Lampung. Kata kunci : Model Pembelajaran Kelompok, Individu, Gerak Dasar Menggiring Bola